Diet is the primary determinant of bacterial community structure in the guts of higher termites. Issue 20 (12th October 2015) - Mikaelyan, Aram; Dietrich, Carsten; Köhler, Tim; Poulsen, Michael; Sillam‐Dussès, David; Brune, Andreas
Abstract The gut microbiota of termites plays critical roles in the symbiotic digestion of lignocellulose. While phylogenetically 'lower termites' are characterized by a unique association with cellulolytic flagellates, higher termites (family Termitidae) harbour exclusively prokaryotic communities in their dilated hindguts. Unlike the more primitive termite families, which primarily feed on wood, they have adapted to a variety of lignocellulosic food sources in different stages of humification, ranging from sound wood to soil organic matter. In this study, we comparatively analysed representatives of different taxonomic lineages and feeding groups of higher termites to identify the major drivers of bacterial community structure in the termite gut, using amplicon libraries of 16S rRNA genes from 18 species of higher termites. In all analyses, the wood‐feeding species were clearly separated from humus and soil feeders, irrespective of their taxonomic affiliation, offering compelling evidence that diet is the primary determinant of bacterial community structure. Within each diet group, however, gut communities of termites from the same subfamily were more similar than those of distantly related species. A highly resolved classification using a curated reference database revealed only few genus‐level taxa whose distribution patterns indicated specificity for certain host lineages, limiting any possible cospeciation between the gut microbiota and host to short evolutionary timescales. Rather, the observed patterns in the host‐specific distribution of the bacterial lineages in termite guts are best explained by diet‐related differences in the availability of microhabitats and functional niches.